2003
DOI: 10.1128/mcb.23.22.7957-7964.2003
|View full text |Cite
|
Sign up to set email alerts
|

The DFNA15 Deafness Mutation Affects POU4F3 Protein Stability, Localization, and Transcriptional Activity

Abstract: A mutation in the POU4F3 gene (BRN-3.1, BRN3C) is responsible for DFNA15 (MIM 602459), autosomaldominant nonsyndromic hearing loss. POU4F3 is a member of the POU family of transcription factors and is essential for inner-ear hair cell maintenance. To test the potential effects of the human POU4F3 mutation, we performed a series of experiments in cell culture to mimic the human mutation. Mutant POU4F3 loses most of its transcriptional activity and most of its ability to bind to DNA and does not function in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 45 publications
3
49
0
2
Order By: Relevance
“…Similar to our POU3F4 results, molecular analyses of POU4F3 mutations identified in DFNA15 patients showed that the mutant POU4F3 proteins lack transcriptional activity due to the loss of nuclear localization and DNAbinding ability (6,35). Thus, the two POU family transcription factors share a common molecular pathological mechanism, whereby transcription of target genes essential for inner ear development is affected.…”
Section: Discussionsupporting
confidence: 65%
“…Similar to our POU3F4 results, molecular analyses of POU4F3 mutations identified in DFNA15 patients showed that the mutant POU4F3 proteins lack transcriptional activity due to the loss of nuclear localization and DNAbinding ability (6,35). Thus, the two POU family transcription factors share a common molecular pathological mechanism, whereby transcription of target genes essential for inner ear development is affected.…”
Section: Discussionsupporting
confidence: 65%
“…In Pou4f3-null mice, hair cells fail to mature and undergo apoptosis during early postnatal development, resulting in mice with auditory or vestibular dysfunction (Erkman et al, 1996;Xiang et al, 1997;Xiang et al, 1998). In addition, mutations in human POU4F3 result in adultonset non-syndromic hearing loss (DFNA15) Pauw et al, 2008;Vahava et al, 1998;Weiss et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that proteasomes are localized in both the nucleus and the cytosol, where intracellular proteins can be degraded by them (16). A number of transcription factors have previously been reported to be degraded in the nucleus (4,9,11,13,28,46,49,63).…”
mentioning
confidence: 99%